A study of the insertion and integration of digital technologies in a community of teachers of a Degree in Pedagogy (Research, Society and Development, 2019)
The goal of paper was analyze how teachers of a Licenciatura Pedagogy Course, use the digital technologies in their pedagogical practice in graduation. We chose a qualitative research, in which the data were collected in a planning week in which the teachers had the task of socializing practices that they develop in the classroom. The analysis and systematization of the data was inspired by the Content Analysis, specifically the grouping procedures by means of themes. The results show that it was possible to understand that the knowledge regarding the different uses of digital technologies in pedagogical practices, still does not fully complement the knowledge set of the professional community of teachers, but is in the process of integration. Accordingly, it is extremely important that the institution continue investing in the continuing education of teachers, with the purpose of promoting innovations in the practices developed in the classroom.